How to interpret and use COVID-19 serology and immunology tests - Ong, David S.Y. (Clin Microbiol Infect, 2021)
BACKGROUND: Although molecular tests are considered the reference standard for coronavirus disease 2019 (COVID-19) diagnostics, serological and immunological tests may be useful in specific settings. OBJECTIVES: This review summarizes the underlying principles and performance of COVID-19 serological and immunological testing. SOURCES: Selected peer-reviewed publications on COVID-19 related serology and immunology published between December 2019 and March 2021. CONTENT: Serological tests are highly specific but heterogeneous in their sensitivity for the diagnosis of COVID-19. For certain indications, including delayed disease presentations, serological tests can have added value. The presence of antibodies against SARS-CoV-2 may indicate a recent or past COVID-19 infection. Lateral flow immunoassay (LFIA) antibody tests have the advantages of being easy and fast to perform, but many have a low sensitivity in acute settings. Enzyme-linked immunosorbent assay (ELISA) and chemiluminescence immunoassays (CLIAs) have higher sensitivities. Besides humoral immunity, cellular immunity is also essential for successful host defences against viruses. Enzyme-linked immunospot (ELISpot) assays can be used to measure T-cell responses against SARS-CoV-2. The presence of cross-reactive SARS-CoV-2-specific T cells in never exposed patients suggests the possibility of cellular immunity induced by other circulating coronaviruses. T-cell responses against SARS-CoV-2 have also been detected in recovered COVID-19 patients with no detectable antibodies. IMPLICATIONS: Serological and immunological tests are primarily applied for population-based seroprevalence studies to evaluate the effectiveness of COVID-19 control measures and increase our understanding of the immunology behind COVID-19. Combining molecular diagnostics with serological tests may optimize the detection of COVID-19. As not all infected patients will develop antibodies against SARS-CoV-2, assessment of cellular immunity may provide complementary information on whether a patient has been previously infected with COVID-19. More studies are needed to understand the correlations of these serological and immunological parameters with protective immunity, taking into account the different circulating virus variants.